Achieving a running cost saving with a cabinet refrigerator incorporating a phase change material by the scheduling optimisation of its cyclic operations. (September 2020) - Maiorino, Angelo; Del Duca, Manuel Gesù; Mota-Babiloni, Adrián; Aprea, Ciro
Highlights: Phase change materials (PCMs) enhanced the operating flexibility of a cabinet refrigerator. Experimental data were used to simulate cyclic operations of the system. A hysteresis scheduling optimisation was performed by simulated annealing (SA). Running cost savings were obtained for different case studies. The off-peak vs. peak cost ratio defines the amount of the achievable saving. Abstract: Phase Change Materials (PCMs) can absorb and release a high amount of energy, and therefore, can be used for shifting electricity demand in some household appliances. Indeed, the use of PCMs in a cabinet refrigerator leads to increase its OFF time and flexibility and moves the energy consumption to other periods for a reduction of the peak energy demand. The higher flexibility of the refrigerator with PCM can be exploited to reduce its running cost considering that many countries adopted Time-of-Use (TOU) tariffs, in which the electricity cost is based on the time of energy use over a day and a week. Hence, this work proposes an algorithm based on Simulated Annealing (SA) method to identify the optimal working scheduling of a refrigerator with PCM to reduce its running costs. Experimental results have been used as inputs for the algorithm, and nine 2-TOU and three 3-TOU electricity tariffs from different European countries have been selected to test the methodology. The possibility to achieve running cost savings for various case studies has been proven. Furthermore, higher is the difference between the peak and off-peak electricity cost; more significant is the economic benefits reached by the proposed method.